2014
DOI: 10.1111/cei.12401
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the T cell immunoglobulin and mucin domain protein 3 pathway exacerbates sepsis-induced immune deviation and immunosuppression

Abstract: SummarySepsis is a life-threatening condition, but the pathophysiological basis and biomarkers for the monitoring of sepsis and as targets for therapy remain to be determined. We have shown previously that T cell immunoglobulin and mucin domain protein 3 (Tim-3), a negative immune regulator, is involved in the physiopathology of sepsis, but the underlying mechanisms remain unclear. In the present study, we showed that Tim-3 signalling modulated the response patterns of both macrophages and T helper cells in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
(97 reference statements)
3
21
0
Order By: Relevance
“…can also activate inflammatory macrophage reactions and promote T cells apoptosis. 26 In this study, we found that Gal-9/Tim-3 axis is largely up-regulated in ALI, which suggests that immune suppression occurs in ALI progression. Noteworthily, our results revealed that DEX exerted a more pronounced role in decreasing Gal-9/ Tim-3 transcriptional expression than NAC, indicating that DEX may relieve ALI-induced immune inhibition and play a potent immunomodulatory effect in ALI.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…can also activate inflammatory macrophage reactions and promote T cells apoptosis. 26 In this study, we found that Gal-9/Tim-3 axis is largely up-regulated in ALI, which suggests that immune suppression occurs in ALI progression. Noteworthily, our results revealed that DEX exerted a more pronounced role in decreasing Gal-9/ Tim-3 transcriptional expression than NAC, indicating that DEX may relieve ALI-induced immune inhibition and play a potent immunomodulatory effect in ALI.…”
Section: Discussionsupporting
confidence: 51%
“…Enhanced Tim‐3 may impair natural killer cells function during endotoxic shock . It has been suggested that Tim‐3 can also activate inflammatory macrophage reactions and promote T cells apoptosis . In this study, we found that Gal‐9/Tim‐3 axis is largely up‐regulated in ALI, which suggests that immune suppression occurs in ALI progression.…”
Section: Discussionsupporting
confidence: 49%
“…The results revealed that IL‐10, IL‐12, and TNF‐α were decreased in the septic shock patients, which indicated that immune function appeared to be ‘exhausted’ following the excessive inflammatory response. Another research has revealed that block the Tim‐3 pathway leads to enhanced pro‐inflammation by macrophage and T‐helper cells polarization and lymphocyte apoptosis . Hence, the increases in Tim‐3 on monocytes in the sepsis and severe sepsis patients were likely intended to maintain immune homeostasis, and this protective mechanism was broken in the septic shock patients as indicated by the decrease in the Tim‐3 levels in this group.…”
Section: Discussionmentioning
confidence: 93%
“…One recent and important feature of lymphocyte anergy in sepsis is the description of various increased co‐inhibitory receptors expressions: PD‐1 (CD279), LAG‐3 (CD223), CTLA‐4 (CD152), TIM‐3, BTLA (CD272) contributing to the definition of T cell exhaustion as that described in chronic viral infections. In septic patients, although only low levels of expressions were observed at the onset of syndrome; over the first week, these expressions were progressively upregulated on lymphocytes .…”
Section: Lymphocytesmentioning
confidence: 99%